Alzheimer Disease Anti-Amyloid Immunotherapies: Imaging Recommendations and Practice Considerations for Monitoring of Amyloid-Related Imaging Abnormalities - Cogswell, Petrice M.; Andrews, Trevor J.; Barakos, Jerome A.; Barkhof, Frederik; Bash, Suzie; Benayoun, Marc Daniel; Chiang, Gloria C.; Franceschi, Ana M.; Jack, Clifford R.; Pillai, Jay J.; Poussaint, Tina Young; Raji, Cyrus A.; et al. (American Journal of Neuroradiology, 2025)
With full FDA approval and Centers for Medicare & Medicaid Services coverage of lecanemab and donanemab, a growing number of practices are offering anti-amyloid immunotherapy to appropriate patients with cognitive impairment or mild dementia due to amyloid-positive Alzheimer disease. The goal of this article is to provide updated practical considerations for radiologists, including implementation of MR imaging protocols, workflows, and reporting and communication practices relevant to anti-amyloid immunotherapy and monitoring for amyloid-related imaging abnormalities (ARIA). On the basis of consensus discussion within an expanded American Society of Neuroradiology (ASNR) Alzheimer, ARIA, and Dementia Study Group, our purpose is the following: 1) summarize the FDA guidelines for the evaluation of radiographic ARIA; 2) review the 3 key MRI sequences for ARIA monitoring and standardized imaging protocols on the basis of ASNR-industry collaborations; 3) provide imaging recommendations for 3 key patient scenarios; 4) highlight the role of the radiologist in the care team for this population; 5) discuss implementation of MRI protocols to detect ARIA in diverse practice settings; and 6) present the results of the 2023 ASNR international neuroradiologist practice survey on dementia and ARIA imaging.ADAlzheimer diseaseAPOEapolipoprotein-EARIAamyloid-related imaging abnormalitiesASNRAmerican Society of NeuroradiologyCMSCenters for Medicare & Medicaid ServicesGREgradient-recalled echo